Comparison of quality of life in university students with different levels of physical activity - Concha-Cisternas, Yeny; Castillo-Retamal, Marcelo; Guzmán-Muñoz, Eduardo (Universidad y Salud, 2019)
Introduction: University students are susceptible to unhealthy lifestyles, which could deteriorate their quality of life (QL). Objective: To compare the QL in university students who have different levels of physical activity (PA). Materials and methods: A descriptive, cross-sectional study that included 126 university students of both sexes from Health, Education and Engineering programs of three universities in Talca (Chile). The QL was assessed through the WHOQOL-BREF questionnaire. A student’s t-test of independent samples was used to compare both the domains of the QL and the baseline characteristics between the groups. The effect size was calculated with Cohen's d. Results: Inactive university students had a higher body mass index (BMI) (p = 0.041). In contrast, active students showed significantly higher scores than inactive ones in overall QL (p=0.002; d=0.67), health QL (p=0.013; d=0.50), physical domain (0.038; d=0.43), psychological domain (p=0.003; d=0.63) and environment domain (p=0.001; d=0.80). Conclusions: Active university students (with moderate and high PA levels) have better overall and health QL. They also have better QL scores in the physical, psychological and environmental domains when compared to inactive students.